Research Trends in PhET Virtual Laboratories Toward Critical Thinking Skills in Physics Learning: A Decade Bibliometric Analysis (2015–2025) - Alia Cahyani; Maria Anastasia Da Lopez; Ziadatun Nikmatillah; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of STEM Education, 2026)
This study aims to analyze research trends in PhET virtual laboratories on critical thinking skills in physics learning during the period 2015–2025. The study used a descriptive quantitative approach with bibliometric analysis methods. Data were obtained from Google Scholar using the Publish or Perish application, then analyzed using VOSviewer. The selection process resulted in 34 articles that met the inclusion criteria. The analysis results show that research has increased significantly since 2020 and peaked in 2025, influenced by the development of digital-based learning after the COVID-19 pandemic and the implementation of the Independent Curriculum. Bibliometric visualization shows that the topics of critical thinking, PhET simulation, and virtual laboratories are the main focus of research, with a tendency to use PhET combined with various learning models such as problem-based learning and guided inquiry. Citation analysis indicates that research examining the effectiveness of PhET use in improving critical thinking skills has a significant impact. However, studies that specifically address critical thinking skills in the context of certain materials or aspects of learning outcomes are still limited. Therefore, this study provides a comprehensive overview of research trends and opens opportunities for the development of more in-depth and focused research in the future.